2003
DOI: 10.1111/j.174-1617.2003.tb00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Fathers and Child Abuse Allegations in the Context of Parental Separation and Divorce

Abstract: Fathers' role in child abuse in the context of parental separation and divorce has been the subject of continuous stereotyping over the last several decades. This article examines the stereotypes projected against current research, particularly findings from a study of an experimental family court program designed for the better management of residence and contact disputes where child abuse allegations had been made. These findings are discussed in regard to similar studies internationally. While the two preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 9 publications
0
27
0
4
Order By: Relevance
“…The review suggested themes of domestic violence, substance abuse and mental illness within the families of the children, but did not undertake separate analysis of the non-accidental injury (or trauma) group. Since other research (Brown & Alexander, 2007;Brown, Frederico, Hewitt, & Sheehan, 1998) has shown that child abuse in the context of parental separation and divorce does not usually become known to Child Protection Services, it would seem likely that filicide victims and their families may not have many, if any, links with Child Protection Services.…”
Section: The Child Protection Services Databasesmentioning
confidence: 95%
See 1 more Smart Citation
“…The review suggested themes of domestic violence, substance abuse and mental illness within the families of the children, but did not undertake separate analysis of the non-accidental injury (or trauma) group. Since other research (Brown & Alexander, 2007;Brown, Frederico, Hewitt, & Sheehan, 1998) has shown that child abuse in the context of parental separation and divorce does not usually become known to Child Protection Services, it would seem likely that filicide victims and their families may not have many, if any, links with Child Protection Services.…”
Section: The Child Protection Services Databasesmentioning
confidence: 95%
“…It has not been considered as a major theme despite recent Australian evidence that shows those filicide victims killed in the context of parental separation and divorce appear to be the largest single group among victims in the filicide population. At the same time, parental separation and divorce has been identified as presenting risks of all types of family violence to children (Brown & Alexander, 2007) though this research has not been linked to filicide. This may be due, in part, to the early research on parental separation and divorce that showed that the impact of parental separation and divorce on parents and children was mostly short term and relatively benign (Wallerstein & Kelly, 1979).…”
Section: The Need For Researchmentioning
confidence: 96%
“…2 On the other hand, during custody disputes mothers do make more allegations of abuse against fathers than fathers do against mothers. There are no overall gender differences in the rates of substantiation, however, which means that mothers are no more apt to make false allegations than are fathers (Brown, 2003;.…”
Section: Ratesmentioning
confidence: 99%
“…There are no dramatic gender differences in rates of suffering physical abuse or neglect (Brown, 2003 Firestone, 2000), although the long-term effects of the abuse may be greater for females than for males (Thompson, Kingree, & Desai, 2004). 7 Both men and women physically abuse and neglect children, but the rates are higher for men.…”
Section: Gender Differences In Physical Abuse and Neglectmentioning
confidence: 99%
See 1 more Smart Citation